Doktrin Allah Tritunggal menurut Injil Yohanes sebagai Analisis Kritis terhadap Paham Kelompok Oneness Pentakosta - Silitonga, Salmineo (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Abstract: This article explains how the doctrine of the trinity outlined in the Gospel of John differs from the group concept of oneness. Oneness is a group that opposes the views of Trinitarians who have a Biblical view. This can be seen in the views specifically regarding the doctrine of the Father, Son, and Holy Spirit, which are different between Oneness Pentecostals and Trinitarians. In this research, the author used descriptive qualitative methods. By collecting data, researching Oneness Pentecostal literature, and then synthesizing these findings. The results of this research are that the Oneness Pentecostal view is different from the Trinitarian view. The concept of difference is that oneness views God the Father, Son, and Holy Spirit as one person. Meanwhile, Trinitarians view that God the Father, Son referring to the theology of the book of John, it certainly clearly reveals the fact that there is an error regarding this view of oneness. and Holy Spirit are different persons but equal in one essence. When referring to the theology of the book of John, certainly clearly reveals the fact that there is an error regarding this view of oneness. Abstrak: Tulisan ini menguraikan bagaimana doktrin ketritunggalan yang diuraikan dalam Injil Yohanes berbeda dengan konsep paham kelompok dari oneness. Oneness adalah kelompok yang menentang pandangan kaum penganut Trinitarian yang memiliki pandangan Alkitabiah. Hal ini terlihat pada pandangan yang khususnya mengenai doktrin Bapa, Anak dan Roh Kudus yang berbeda antara Oneness Pentakosta dengan Trinitarian. Dalam penelitian ini penulis menggunakan metode kualitatif deskriptif. Dengan cara pengumpulan data-data meneliti literature Oneness Pentakosta dan kemudian mensintesakan temuan-temuan tesebut. Hasil penelitian ini adalah bahwa pandangan Oneness Pentakosta berbeda dengan pandangan Trinitarian. Konsep perbedaan itu bahwa Oneness berpandangan Allah Bapa, Anak dan Roh Kudus adalah satu Pribadi. Sedangkan kaum Trinitarian berpandangan Allah Bapa, Anak dan Roh Kudus adalah pribadi yang berbeda tetapi sederajat dalam satu hakekat. Apabila merujuk pada Teologis kitab Yohanes tentunya jelas mengungkapkan suatu fakta kekeliruan terhadap pandangan oneness ini.